2016
DOI: 10.1007/s13197-016-2316-7
|View full text |Cite
|
Sign up to set email alerts
|

3-Butenyl isothiocyanate: a hydrolytic product of glucosinolate as a potential cytotoxic agent against human cancer cell lines

Abstract: The present study envisages the cytotoxic potential of 3-butenyl isothiocyanate isolated from Brassica juncea L. Czern var. Pusa Jaikisan against the human cancer cell lines viz. prostate, bone osteosarcoma, cervical, liver, neuroblastoma and breast cancer. As the compound was observed to be more effective against prostate cancer cell line, therefore, this cell line was further used to study the mechanism of cell death using neutral red assay, reactive oxygen species assay, mitochondrial membrane potential ass… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
19
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 30 publications
(19 citation statements)
references
References 26 publications
0
19
0
Order By: Relevance
“…There are a few studies on the effects of 3-BI on cancer cells under in vitro conditions (26,30,35). Other 3-butenyl ITCs, including 4-methylthio-3-BI-ITC (raphasatin) or 4-methylsulfinyl-3-BI-ITC (sulforaphene), have been found not to cause toxicity in T lymphocytes, despite being cytotoxic in Unlike other ITCs, the molecular mechanisms by which 3-BI produces an inhibitory effect on the survival and proliferation of cancer cells are not fully known.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…There are a few studies on the effects of 3-BI on cancer cells under in vitro conditions (26,30,35). Other 3-butenyl ITCs, including 4-methylthio-3-BI-ITC (raphasatin) or 4-methylsulfinyl-3-BI-ITC (sulforaphene), have been found not to cause toxicity in T lymphocytes, despite being cytotoxic in Unlike other ITCs, the molecular mechanisms by which 3-BI produces an inhibitory effect on the survival and proliferation of cancer cells are not fully known.…”
Section: Discussionmentioning
confidence: 99%
“…1). ITCs have inhibitory effects on the metabolic activation of carcinogenic dietary or tobacco components (24), along with the inhibition of mutagenesis (25) and anti-carcinogenic effects in vitro (26)(27)(28)(29)(30) and in vivo (31,32). In PC, ITCs modulate epigenetic changes, induce the arrest of the cell cycle, activate apoptosis pathways and increase chemotherapeutic agent sensitivity; leading to the inhibition of cell proliferation, progression and invasionmetastasis (33).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…In fact, health-promoting values are from the hydrolysis products of glucosinolates rather than glucosinolates themselves. For instance, 3-butenyl isothiocyanate, a hydrolysis product of an aliphatic glucosinolate gluconapin, was reported to have antiproliferative activity against human prostate, lung, cervical, liver, and breast cancers, as well as human neuroblastoma and osteosarcoma cell lines [30]. Indole-3-carbinol, a hydrolysis product of glucobrassicin which was one of the major glucosinolates in the kale and collard cultivars used in this study, has been reported for its beneficial effect against obesity in mice [31,32].…”
Section: Glucosinolatesmentioning
confidence: 99%
“…Pusa Jaikisan, which contains 3-butenyl isothiocyanate. However, in the latter study, an increase in caspase-3 activity was also observed in PC-3 cells [38].…”
Section: Effects Of Extracts From Specific Plant Families On Human Prmentioning
confidence: 53%